2021
DOI: 10.1111/ejn.15157
|View full text |Cite
|
Sign up to set email alerts
|

Role of anatomical insular subdivisions in interoception: Interoceptive attention and accuracy have dissociable substrates

Abstract: Prior neuroimaging studies have supported the idea that the human insular cortex plays an important role in processing and representing internal bodily states, also termed “interoception.” According to recent theoretical studies, interoception includes several aspects such as attention and accuracy. However, there is no consensus on the laterality and location of the insula to support each aspect of interoception. Thus, we aimed to identify the anatomical insular subdivisions involved in interoceptive attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 61 publications
8
31
0
Order By: Relevance
“…First, this non-linear association suggests that self-reported interoceptive attention and accuracy are indeed separate constructs, although likely influenced by each other. This is in line with recent evidence that found that interoceptive attention and accuracy are associated with dissociable insular subdivisions (bilateral dorsal mid-anterior insula vs. dorsal anterior portion of the right insula, respectively) which are vastly interconnected (Haruki & Ogawa, 2021). Secondly, it is important to further refine what is driving this association, that is, whether it may be a true non-linear association between selfreported interoceptive attention and accuracy or if these results are due to differences across both questionnaires (e.g., each measure assesses somewhat different interoceptive signals).…”
Section: A Quadratic Association Between Self-reported Interoceptive Attention and Accuracy?supporting
confidence: 92%
“…First, this non-linear association suggests that self-reported interoceptive attention and accuracy are indeed separate constructs, although likely influenced by each other. This is in line with recent evidence that found that interoceptive attention and accuracy are associated with dissociable insular subdivisions (bilateral dorsal mid-anterior insula vs. dorsal anterior portion of the right insula, respectively) which are vastly interconnected (Haruki & Ogawa, 2021). Secondly, it is important to further refine what is driving this association, that is, whether it may be a true non-linear association between selfreported interoceptive attention and accuracy or if these results are due to differences across both questionnaires (e.g., each measure assesses somewhat different interoceptive signals).…”
Section: A Quadratic Association Between Self-reported Interoceptive Attention and Accuracy?supporting
confidence: 92%
“…One possible explanation is that the primary interoceptive cortex would respond to changes in bodily states, rather than subjective experience of them: a recent study using rodents revealed that almost all neurons in the posterior insula responded to physiological changes (Cechetto and Saper, 1987; Gehrlach et al, 2019). In fact, interoceptive attention task where participants focus on their ongoing bodily sensations has been found to consistently activate the middle insula but the posterior (Haruki and Ogawa, 2021; Simmons et al, 2013). Rather, the posterior insula has been found to be functionally disconnected from other brain regions when people with accurate interoception performed the interoceptive attention task (Kuehn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Even when the brain activation of another modality of interoception (such as gastric or urinary) was measured, direct comparison of brain activation within the modality of interoception has not been discussed (Deville et al, 2020; Kerr et al, 2016; Simmons et al, 2013). Therefore, understanding of how the brain encodes and represents different types of interoception is still limited; for example, the right anterior insula has been suggested as the most relevant region for the subjective experience of cardiac interoception (Caseras et al, 2013; Pollatos et al, 2007) but some studies have questioned the generalizability of this relationship for another modality of interoception (Baltazar et al, 2021; Haruki and Ogawa, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies of heartbeat detection have linked individual differences in the functioning of several regions including the midbrain, ventral striatum, anterior cingulate cortex, somatosensory cortex, and the insula to greater interoceptive accuracy [e.g., ( 41 , 63 , 67 , 94 )]. From among these areas, the right dorsal anterior insula appears to be the most reliably positively associated with interoceptive accuracy across studies ( 41 , 63 , 95 ). It has been proposed that this insular subregion may contribute to instantaneous subjective feelings from the body that generate a sense of the present moment ( 40 , 67 ).…”
Section: Dimensions Of Interoceptionmentioning
confidence: 97%